An unusual presentation of a stroke in a developing country: a case report. (December 2017) - Ehelepola, N.; Ranasinghe, T.; Prashanthi, B.; Bandara, H.
Abstract Background Patients often, but not always, present with features that allow easy differentiation between traumatic brain injury and a stroke. Early diagnosis and appropriate treatment are crucial for a good outcome in both. Millions of people worldwide climb coconut and other trees without any protective gear. We present a case of a coconut tree climber found unconscious after a fall, initially misdiagnosed as a traumatic brain injury but later proven to be a hemorrhagic stroke. We discuss how to prevent such incidents and why that deserves more attention. There is a severe paucity of such case reports and discussion of related issues in medical literature. Case presentation A 65 year old, previously healthy Sinhalese man had fallen from a coconut tree and was found unconscious with wounds on his limbs on the right side of his body. He was taken to the closest hospital. After being given primary care, he was transferred to the Kandy teaching hospital for neurosurgical management. Physical examination findings suggested a stroke but not the medical history. We could not exclude a head and cervical spine injury clinically. A computed tomography scan of the brain and cervical spine showed a left thalamic hemorrhage but no other injuries that could be attributed to trauma, therefore we confirmed it was a hemorrhagic stroke presenting as a traumatic brain injury. Conclusion Since strokes are very common and rising in prevalence, being more aware of uncommon presentations like this can be useful to all health care workers working in acute medical settings especially in developing countries. Computed tomography scans of the brain plays a critical role in accurate diagnosis of both strokes and traumatic brain injuries; but many people in the developing world do not have prompt access to computed tomography scanners. Providing early access to a computed tomography scan of the brain to a wider population after a head injury or a stroke may contribute to reducing morbidity and mortality. Developing and promoting affordable and simple safety methods for palm and other tree climbers can also help to reduce morbidity and mortality.